Sinkretisme NU dan Muhammadiyah dalam Pendidikan Islam Papua - Hasruddin Dute; M. Zainul Hasani Syarif; Muhamad Thoif (Al-Fikr: Jurnal Pendidikan Islam, 2021)
Syncretism from the past until now is still a topic of discussion in a study. At first syncretism existed only in the fields of religion and philosophy, but now it is developing in the educational aspect. This can be seen in educational institutions in Papua, especially the Papuan Islamic Education Foundation. This study uses qualitative analytical research with a historical approach. The results of this study indicate that Yapis Papua was founded on the initiation of community organizations and Islamic leaders who are in the NU and Muhammadiyah community organizations. The two organizations and Islamic leaders together building the Papuan community through education by establishing the Yapis Papua educational institution and now there are 193 schools and 5 universities in Papua. This collaboration occurs because the existing Islamic schools have not been recognized because they are only local and partial so they do not have a parent foundation throughout the land of Papua.